Decentralized premix fuel management and the development of coastal communities in the Komenda-Edina-Eguafo-Abirem Municipality - Sam, Ohenewaa Eunice (2015)
A thesis submitted to the School of Graduate Studies Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the degree of Master of Philosophy in Planning